Identification of Science Teacher Practices and Barriers in Preparation of Minimum Competency Assessment in the Covid-19 Pandemic Era - Hayuni Retno Widarti; Deni Ainur Rokhim; Maya Oki Septiani; Mohammad Hilfi Azra Dzikrulloh (Orbital: The Electronic Journal of Chemistry, 2022)
The Minister of Education, Culture, Research, and Technology made a new policy that from 2021, a national assessment that will be held is minimum competency assessment or commonly known as AKM. AKM is measuring two basic skills that are literacy and numeracy. The occurrence of the Covid-19 pandemic has affected the implementation of education. The learning that was originally face-to-face in the classroom now must be changed to online system. This is causes delays in the preparation of minimum competency assessment. Therefore, this research is important to do so that teachers, schools, and the government have a strategy in preparing minimum competency assessments in the era of the pandemic and post-covid-19 pandemic. This study aims to identify the practices and barriers of science teachers in preparation for the minimum competency assessment during the Covid-19 pandemic. This study uses a qualitative descriptive research method with four stages of research, that is preparation, data collection, data analysis, and concluding. The subject in this research included 15 science teachers from East Java, Indonesia. Subject selection was carried out using criterion-based selection and sample determination using cluster sampling technique. The instrument uses consist of an open and closed questionnaire via a google form. Data was analyzed using descriptive statistical techniques. The result showed that in online learning, most teachers had implemented learning that oriented to the preparation of minimum competency assessment but had not shown a positive correlation to student learning outcomes.DOI: http://dx.doi.org/10.17807/orbital.v14i1.1695